Ameloblastic Fibrodentinoma Presenting as a False Gingival Enlargement in the Maxillary Anterior Region - Shiny Joseph; Lakshmi Priya; Dinesh Gopal; Mary Devachen; Ajay Narayan; Muhammed Afnan (Hindawi Limited, 2015)
Ameloblastic fibrodentinoma is a rare benign mixed odontogenic neoplasm usually occurring in the first two decades of life. It is more common in males and the most common site of occurrence is in the mandibular premolar molar area. This report presents a case of ameloblastic fibrodentinoma in a 12-year-old boy in the maxillary anterior region, a less common site for the occurrence of ameloblastic fibrodentinoma. A 12-year-old boy presented with a midline diastema in 11 and 21 region and a swelling in the palatal aspect of 11 and 12. Intraoral periapical radiograph showed the presence of rarefaction of bone on the mesial aspect of the cervical and middle third of the root of 11. Excision biopsy was done. The specimen was processed and stained with hematoxylin and eosin. Microscopic examination showed islands, chords and strands of odontogenic epithelium in a primitive ectomesenchyme resembling dental papilla. The odontogenic epithelium exhibited peripheral ameloblast-like and central stellate reticulum-like cells. The presence of dentinoid material was seen adjacent to the odontogenic epithelium in some foci. The lesion was diagnosed as ameloblastic fibrodentinoma.